E-Money in Worldview Perspective Maqashid Sharia - Imam Kamaluddin; Tito Noer Islami (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In the 20th century, technological developments experienced very significant growth and brought winds of change to human life in all aspects, such as culture, law, education or economic aspects. The emergence of the digitalization of money is a form of technological development in this era. Electric Money or what is usually shortened to e-money is a trend in terms of buying and selling transactions. As Muslims, we are obliged to carry out all our work in accordance with the provisions that Allah SWT has determined. As for what Allah SWT has determined, it has a sharia maqashid that its servants must know. In carrying out e-money transactions, it is necessary to know the sharia maqashid contained therein. This research aims to find out more about how e-money is from a sharia maqashid perspective. This research uses the qualitative literature study method. The results of this research are that in e-money there is an element of benefit that is a sharia maqashid that can meet human needs, namely hifdzul maal. There are several negative impacts in e-money that need to be avoided in order to maintain the value of maal hifdzul, such as device duplication, theft and malfunction.